Socio-religious interaction of the Patoman Village community as a contextual learning resource in Islamic religious education - Lutpita Firdatul Jannah; Aulia Nazar (Privietlab, 2026)
This study explores the practice of socio-religious interaction in Patoman Village, Blimbingsari District, Banyuwangi, as a contextual learning resource in Islamic Religious Education or Pendidikan Agama Islam (PAI). The background of this study lies in the need for PAI learning that is not merely normative and textual but also contextual, applicable, and responsive to the realities of a multicultural society. Unlike previous studies that primarily discuss Patoman Village as a case of interreligious harmony or multicultural coexistence, this article positions the socio-religious interactions in Patoman Village as an analytical basis for constructing locality-based contextual learning resources in Islamic Religious Education. This study employed a qualitative approach using library research. It does not rely on primary field data such as interviews or direct observations. Instead, it analyzes previous studies, academic articles, books, and relevant documents concerning Patoman Village, socio-religious interaction, religious moderation, and contextual learning in Islamic Religious Education. The collected literature was analyzed through descriptive thematic synthesis to identify documented socio-religious values and reinterpret their relevance for contextual PAI learning. The literature synthesis indicates that the socio-religious interactions documented in Patoman Village, such as interfaith dialogue, social cooperation, and mutual respect, represent Islamic values such as ukhuwah basyariyah, tasamuh, and ta'awun. These values have great potential to be used as contextual learning resources in PAI to shape the character of students to be moderate, inclusive, and adaptive to diversity. The recommendation from this study is the need for the integration of locality-based socio-religious values into the curriculum and learning methods of Islamic Religious Education, as a concrete effort to strengthen character education and build social harmony in a pluralistic society.